2015
DOI: 10.1039/c5ra03401a
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary semiconductor Cu2ZnSnS4 loaded with MoS2 as a co-catalyst for enhanced photo-catalytic activity

Abstract: A composite photocatalyst of Cu2ZnSnS4 (CZTS) containing 1% MoS2 is prepared by hydrothermal reaction using Cu(OAc)2, Zn(NO3)2, and SnCl2 in a H2O/en (9:1) solution to which SC(NH2)2 is added dropwise (autoclave, 180 °C, 24 h).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 42 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…As can be seen from Figure S5 for CuInS 2 and ~0.60 mA cm −1 for CdSe. 59 It confirms the presence of excited-state electronic interactions between CZTS and MoS 2 entities in CZTS-MoS 2 composite, leading to the deactivation of excited state of CZTS via non-radiative process involving the charge transfer from CZTS to MoS 2 . We have deposited CuInS 2 QDs in a period of ~2-3 min, while ~30 min was fixed to load CdSe QDs.…”
Section: Wavelength (Nm)supporting
confidence: 61%
“…As can be seen from Figure S5 for CuInS 2 and ~0.60 mA cm −1 for CdSe. 59 It confirms the presence of excited-state electronic interactions between CZTS and MoS 2 entities in CZTS-MoS 2 composite, leading to the deactivation of excited state of CZTS via non-radiative process involving the charge transfer from CZTS to MoS 2 . We have deposited CuInS 2 QDs in a period of ~2-3 min, while ~30 min was fixed to load CdSe QDs.…”
Section: Wavelength (Nm)supporting
confidence: 61%
“…Meanwhile, the noble metal based oxides (e.g., RuO 2 , IrO x ), cost‐acceptable cobalt based species (e.g., CoO x , Co(II), Co(OH) 2 , Nocera Co–Pi), MnO x FeOOH, and NiOOH have been demonstrated to be excellent water‐oxidation co‐catalysts to boost the photocatalytic O 2 evolution over different semiconductors. Similarly, various possible co‐catalyst‐modification strategies, such as noble metals (Pt, Au, Ag), H 3 BO 3 , H 3 PO 4 , MoS 2 , graphene, Cu(II)/Fe(III) clusters, and their hybrids have been extensively employed to improve the O 2 adsorption and reduction on photocatalysts, thus facilitating more efficient capture of the photogenerated electrons for further improved photo‐degradation activities. In addition, the noble metals/alloys (Pt, Au, Ag, Pd, and Cu x Pt y ), earth‐abundant metal compounds (Cu 2 O, NiO x , Ni@NiO), graphene, complex, and their composites have been widely employed as co‐catalysts to improve the photocatalytic activity and selectivity for CO 2 reduction.…”
Section: Fundamental Mechanism Of Heterogeneous Photocatalysismentioning
confidence: 99%
“…Feng Jiang et al reported a multilayer of Pt/In 2 S 3 /CdS/CZTS heterostrucures, where the obtained photocathode showed significant enhancement in terms of stability during photoirradiation for PEC water splitting [ 21 ]. Hybridized 1T-2H MoS 2 was then added to provide higher electrical conductivity and the specific surface area necessary to achieve superior catalytic ability [ 22 , 23 , 24 ]. Importantly, Ag was added in the structure to extend the light absorption of the photocatalyst to the visible light region, which was due to the surface plasmon resonance of Ag NPs, which enabled the photocatalyst to absorb light in the visible spectrum.…”
Section: Introductionmentioning
confidence: 99%